Cesare Brandi's Theory of Restoration and Azulejos - Mimoso, J. (2009)
Though Cesare Brandi, author of the capital "Theory of Restoration" never mentioned glazed tiles in the main core of his work, his theory applies generally to art heritage (both narrative art and architecture). The communication is a theoretical exercise on the restoration of azulejo panels, particularly the treatment of lacunae, at the light of Cesare Brandi's principles.